2013
DOI: 10.4161/auto.25063
|View full text |Cite
|
Sign up to set email alerts
|

Functions of autophagy in normal and diseased liver

Abstract: Autophagy has emerged as a critical lysosomal pathway that maintains cell function and survival through the degradation of cellular components such as organelles and proteins. Investigations specifically employing the liver or hepatocytes as experimental models have contributed significantly to our current knowledge of autophagic regulation and function. The diverse cellular functions of autophagy, along with unique features of the liver and its principal cell type the hepatocyte, suggest that the liver is hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
402
2
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 407 publications
(412 citation statements)
references
References 329 publications
(460 reference statements)
4
402
2
4
Order By: Relevance
“…While autophagy helps to prevents tumorigenesis, it is also used by the cancer cells for survival against apoptosis by traditional chemotherapeutic drugs [303,304] . Initially, autophagy functions are as a tumor suppressor and later, when HCC has developed, the autophagy may contribute to its growth [303,305] . Microbes have evolved mechanisms to evade and exploit autophagy and both HBV and HCV use autophagy for their own survival [306] .…”
Section: Resultsmentioning
confidence: 99%
“…While autophagy helps to prevents tumorigenesis, it is also used by the cancer cells for survival against apoptosis by traditional chemotherapeutic drugs [303,304] . Initially, autophagy functions are as a tumor suppressor and later, when HCC has developed, the autophagy may contribute to its growth [303,305] . Microbes have evolved mechanisms to evade and exploit autophagy and both HBV and HCV use autophagy for their own survival [306] .…”
Section: Resultsmentioning
confidence: 99%
“…26 It is noteworthy that obesity and hepatic steatosis, diseases closely associated with mitochondrial and autophagic dysfunction, 27 are mechanistically linked to hyperacetylation of mitochondrial proteins. 28,29 Here we provide evidence that removing acetyl group of MFN2 by SIRT1 plays a pivotal role in hepatocyte autophagy and survival after I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…46 Although autophagy is generally thought to be a cell survival pathway against various adverse stresses, 9,46 it has been reported that a general caspase inhibitor ZVAD induced autophagic cell death in a cell culture model. 47 However, a later study found that ZVAD did not induce autophagy but instead blocked autophagosome maturation and induced necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…6e8 Autophagy is a catabolic lysosomal degradation pathway, which plays a critical role in normal liver physiology and liver diseases. 9 Autophagy involves the formation of doublemembrane autophagosomes that engulf intracellular proteins and organelles and then fuse with lysosomes to form autolysosomes, where enveloped cargo is degraded. Although under certain specific conditions autophagy may contribute to cell death, 10 the liver basal autophagy seems to act as a cell survival function and is critical to maintain liver homeostasis.…”
mentioning
confidence: 99%